ANALYSIS OF THE INFLUENCE OF ORDER VARIATION FACTORS ON THE COSTS AND TIME OF IMPLEMENTING CHANNEL DIVERCTION INFRASTRUCTURE CONSTRUCTION PROJECTS IN RESIDENTIAL AREAS - Ghazi Ghossan Hindami; Agus Suroso; Mawardi Amin (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
Tangerang is a big city in Indonesia. The housing sector rocketing in this region. Changes in development often occur because problems arise and have an impact on costs and time. Researchers focused on finding the cause of the work diverting residential channels being hampered. For this reason, changes were made to the sheetpile design and changes to the infrastructure mobilization method to meet the contract time. The research uses the SEM PLS method to determine the factors causing order variations. In addition, the data processing application was used to determine the effect of order variations on time and cost performance. The respondents were 60 owners and consultants. Based on the results of the cost performance analysis, additional work arising from order variations reached 10,516,305,346 IDR and reduced work due to order variations reached 6,628,461,533 IDR or around 12.96% of the initial contract price and the results of time performance analysis for time losses that occurred due to order variations on the project showed an additional time of 5 months or 125%.